2018
DOI: 10.3892/etm.2018.6316
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key genes and pathways for esophageal squamous cell carcinoma by bioinformatics analysis

Abstract: The aim of the present study was to identify the differentially expressed genes (DEGs) in esophageal squamous-cellcarcinoma (ESCC) and provide potential therapeutic targets. The microarray dataset GSE20347 was downloaded from the Gene Expression Omnibus (GEO) database, and included 17 tissue samples and 13 normal adjacent tissue samples from patients with ESCC. A total of 22,277 DEGs were identified. A heat map for the DEGs was constructed with the Morpheus online tool and the top 200 genes (100 upregulated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 50 publications
(40 reference statements)
2
10
0
Order By: Relevance
“…Based on their absolute values of LogFC, a total of 50 genes were selected from the DEGs, followed by analyzing with the Morpheus () online software to construct the heat map (Figure 2) [9]. Furthermore, the biological processes functional enrichment and pathway enrichment analyses for DEGs were investigated using FunRich () software [10].…”
Section: Resultsmentioning
confidence: 99%
“…Based on their absolute values of LogFC, a total of 50 genes were selected from the DEGs, followed by analyzing with the Morpheus () online software to construct the heat map (Figure 2) [9]. Furthermore, the biological processes functional enrichment and pathway enrichment analyses for DEGs were investigated using FunRich () software [10].…”
Section: Resultsmentioning
confidence: 99%
“…CDCA3 is essential to regulate plenty of physiological and pathological processes by stimulating the proteins degradation like transcription factors and signal transduction molecules [33], and exert an important role during various cancer types development [19,22]. Some researches indicated that CDCA3 was markedly overexpressed accompanied by poor prognosis in NSCLC, and exerted a vital part during tumorigenesis and esophageal carcinoma development [34]. Zhang Y et al found that CDCA3 upregulation accelerated the cell proliferation and colony formation, while CDCA3…”
Section: Discussionmentioning
confidence: 99%
“…Till now, with the development of high-throughput sequencing technology, gene expression profiling has been widely used to identify genes or signal pathway related to the development of esophageal cancer [47][48][49][50][51][52]. However, most studies only identified DEGs or signaling pathways, which might be involved in esophageal cancer development based on different GEO datasets.…”
Section: Discussionmentioning
confidence: 99%